A new species of Choroterpes (Ephemeroptera: Leptophlebiidae) from a tropical stream of south India - Dinakaran, S.; Balachandran, C.; Anbalagan, S. (Zootaxa, 2009)
Choroterpes alagarensis new species (type locality: Alagar hill, Madurai) (Ephemeroptera: Leptophlebiidae) is described from male and female imago, sub imago and nymphs. This species is found in leaf packs, woody debris, pebbles and boulders and occurs in slow flowing stream areas.